WEBSITE SEBAGAI ALAT PROMOSI UNTUK PARIWISATA BERBASIS SEJARAH: STUDI KASUS TAMAN ARKEOLOGI LEANG-LEANG, MAROS, SULAWESI SELATAN - Putri Salzabila Rahman; Darmayasa; Andi Abriani; Agus (Wonderful-Journal of Tourism Destination, 2026)
Leang-Leang Archaeological Park in Maros Regency, South Sulawesi, is an important archaeological site with ancient cave paintings that require better promotion and information. This study aims to design a website as an information and promotion medium that can provide easier and more comprehensive access for tourists. The research uses a qualitative approach with a development method, namely Research and Development (R&D). Data were collected through interviews, observations, and documentation to design a website that meets the users' needs. The results show that the designed website can enhance visitors' experiences by providing complete and easily accessible information, such as history, location, facilities, and an interactive map. The website also offers interactive features that support visitor engagement. The findings indicate that the website can improve promotion and awareness of the importance of preserving the archaeological site. This research contributes to the development of digital media for historical and cultural tourism, and provides a model for other archaeological site managers to utilize technology for preservation and promotion.